English Passive Voice: An X-Bar Theory Analysis - Wittaningsih, Aprilia (Indonesian Journal of English Language Studies (IJELS), 2018)
English passive voice has its own pattern. Some says that the pattern comes from the active form then it is changing. However, it is rather difficult to memorize the pattern, especially for the non-native people. X-bar theory is one way that can be used in understanding the passive form. By using X-bar diagram, the D- structure of the sentence can be seen and then moved into certain position which makes the S-structure of passive form. This study aims to see what movements exist in the English passive constructions and if there is any of special case. By giving the examples and the X-bar diagrams of basic form of passive, passive form of future tense, passive form of continuous tense, the special case inserting the word ‘by’, and also the use of word ‘get’; the construction of passive form will be clearly and easily understood.Keywords: passive voice, X-bar theory, S-structure, D-structure, movement